Freshwater Clam Extract Ameliorates Triglyceride and Cholesterol Metabolism through the Expression of Genes Involved in Hepatic Lipogenesis and Cholesterol Degradation in Rats. (12th February 2013) - Laurent, Thomas; Okuda, Yuji; Chijimatsu, Takeshi; Umeki, Miki; Kobayashi, Satoru; Kataoka, Yutaro; Tatsuguchi, Iwao; Mochizuki, Satoshi; Oda, Hiroaki
Abstract : The freshwater clam ( Corbicula spp.) is a popular edible bivalve and has been used as a folk remedy for liver disease in Asia. As a Chinese traditional medicine, it is said that freshwater clam ameliorates alcoholic intoxication and cholestasis. In this study, to estimate the practical benefit of freshwater clam extract (FCE), we compared the effects of FCE and soy protein isolate (SPI) on triglyceride and cholesterol metabolism in rats. FCE and SPI lowered serum cholesterol, and FCE tended to reduce serum triglycerides. FCE enhanced fecal sterol excretion and hepatic mRNA levels of CYP7A1 and ABCG5 more substantially than SPI; however, both diets reduced hepatic cholesterol. Both of the diets similarly suppressed liver lipids improved Δ9-desaturated fatty acid profile, and FCE was associated with a reduction in FAS and SCD1 mRNA levels. Hepatic transcriptome analysis revealed that inhibition of lipogenesis-related gene expression may contribute to downregulation of hepatic triglycerides by FCE. FCE would have better potential benefits for preventing metabolic disorders, through greater improvement of metabolism of triglycerides and cholesterol, likely through a mechanism similar to SPI.